Methodology of development of physical qualities in highly skilled judokers - Khajibayev, Jurabek (Science and Education, 2024)
This in the article qualified of judokas physical readiness improvement methodology and his efficiency experimental justification according to conclusions given is the results and belongs to practical recommendations illuminated.